Media as a promotion tool for electronic government and services (Herald of Journalism, 2020)
Population in the modern society are no longer to seek the information and other documental ser- vices by themselves. Appearing of electronic devices and services enlighten people’s life, so the im- provement and development of it is vital. Media becomes the basic instrument in realizing this process and let users to be aware of last news and changes. Therefore, it is the relevant problem of research work. The aim of article is to explain the role of media in promotion of electronic services. Basic scientific  and practical directions include all mention of electronic services and government in mass media, ad- vertising in social media and recognition in environment, also it was defined the main tasks of research article. Apart from written theories, the author took the questionnaire from citizens of 18-30 years duringthe work process.Whilst writing the scientific research, there were analyzed and concluded publishing and advertising of e-services through media tools. Mobile application and version in social networking services were compared that provide to opening up of drawback and best qualities. So methodology used in given article is more qualitative than quantitative because of using numbers, analysis and amount of users related to this scientific work.Expected result is to identify how much people operate the electronic services or e-Gov at that mo- ment and what type of media is more influent in this case. Worth and practical meaning of research work are Studying the true numbers taken from real time sites and application. The value of making research paper is associated with direct contact of real users rather than taking facts from Internet. Conclusion of scientific work links with numbers and facts that would be used in following development of electronic government and services through mass media.
Keywords: electronic government, media tools, social networking services, electronic services.